Editorial. Issue 2 (1st December 2021) - Abrams, Benjamin; Gardner, Peter R.
Abstract : This issue is—in many ways—united by a common theme: revisiting the past and rethinking the problems it poses. Beginning with a renewed test of the biographical availability hypothesis, moving through a reassessment of the dynamics of collective identity formation, and stopping at a re-evaluation of the legacies of the 2011 protest wave, this issue begs that we reconsider that which we thought we already knew and open our minds to novel nuance and differential dynamics. It is thus fitting that it closes with a reflection on the life's work of William Gamson, whose work prompted a great many scholars of social movements and contentious politics to reassess and re-evaluate much that we had assumed to know over the years.